ANALISIS STORE ATMOSPHERE DAN PROMOTION YANG BERPENGARUH TERHADAP REVISIT INTENTION DI THELAPAN COFFEE BANDUNG - Nur Ummu Syalamah Pratami; Caria Ningsih; Gilang Pratama Putra (Akademi Pariwisata NHI Bandung, 2023)
This research aims to find out how the impact of Store Atmosphere and promotion on revisit intention at Thelapan Coffee Bandung. Store Atmosphere is a series of atmosphere experiences that are felt by consumers from the first time they come to the coffee shop until they finish enjoying the dishes and the atmosphere at the coffee shop. While promotion is an activity to attract consumers to come or intend to come back so that a transaction can occur. The independent variable (X1) is store atmosphere which has 4 elements including store layout, exterior, general interior, and interior display (Berman and Evan, 2015), then the independent variable (X2) is promotion, promotion has 6 dimensions, including advertising, personal selling, sales promotion, public relations, word of mouth, and direct marketing (Ailijaa F R et al., 2020). The dependent variable (Y) in this research is revisiting intention with dimensions of revisit propensity, revisit willingness, and revisit probability shortly (Zhang et al., 2018). This study uses quantitative and explanatory survey methods, in this study, 100 respondents had transacted at Thelapan Coffee Bandung. The data processing technique uses validity and reliability tests, classical assumption tests, and multiple linear regression tests with f test (simultaneous), and t-test (partial). The results of the study simultaneously show that store atmosphere and promotions have a significant effect on revisit intentions. And the results partially show that store atmosphere has no significant effect, while promotion has a significant effect on revisit intentions.